1997
DOI: 10.1074/jbc.272.29.18007
|View full text |Cite
|
Sign up to set email alerts
|

The Acidic Region of the Factor VIII Light Chain and the C2 Domain Together Form the High Affinity Binding Site for von Willebrand Factor

Abstract: A binding site for von Willebrand factor (vWf) was previously localized to the carboxyl terminus of the C2 domain of the light chain (LCh) of factor VIII (fVIII). The acidic region of the LCh, residues 1649 -1689, also controls fVIII⅐vWf binding by an unknown mechanism. Although anti-acidic region monoclonal antibodies prevent formation of the fVIII⅐vWf complex, the direct involvement of the acidic region in this binding has not been demonstrated. By limited proteolysis of LCh with Staphylococcus aureus V8 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
189
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(199 citation statements)
references
References 44 publications
9
189
0
1
Order By: Relevance
“…Alternatively, it is possible that the amino-terminal acidic region of the A3 domain of FVIII may be closely associated with the C2 domain in the threedimensional conformation. vWF-binding sites are known to be located in both the C2 and A3 domains, and FVIII and vWF association is enhanced by the presence of both regions (34). The present anti-C2 antibody, therefore, might have inhibited thrombin cleavage in the amino-terminal A3 region.…”
Section: Competitive Inhibition Of Thrombin Proteolysis Of Lch Bymentioning
confidence: 99%
“…Alternatively, it is possible that the amino-terminal acidic region of the A3 domain of FVIII may be closely associated with the C2 domain in the threedimensional conformation. vWF-binding sites are known to be located in both the C2 and A3 domains, and FVIII and vWF association is enhanced by the presence of both regions (34). The present anti-C2 antibody, therefore, might have inhibited thrombin cleavage in the amino-terminal A3 region.…”
Section: Competitive Inhibition Of Thrombin Proteolysis Of Lch Bymentioning
confidence: 99%
“…The binding of FVIII to vWF is important for the survival of FVIII as the plasma concentration of FVIII is considerably reduced in the absence of vWF (6)(7)(8). FVIII binds to vWF involving A3 and C2 domains of the light chain (9)(10)(11)(12)(13). It has been shown that the A2, A3, and C2 domains of FVIII are involved in the interaction with LRP (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Upon proteolytic activation, FVIIIa is released from VWF as a heterotrimer composed of the A1 and A2 domains plus the FVIIIa light chain, A3-C1-C2. Activated platelet membranes expose negatively charged phosphatidylserine (PS), which increases from 2% to 10% or more of the surface phospholipids upon activation.…”
Section: Introductionmentioning
confidence: 99%